2000
DOI: 10.1007/s002340000431
|View full text |Cite
|
Sign up to set email alerts
|

A ring-enhancing metastasis with central high signal on diffusion-weighted imaging and low apparent diffusion coefficients

Abstract: Diffusion-weighted imaging (DWI) has been reported to be useful in the differential diagnosis between abscesses and cystic or necrotic tumours. However, experience is still limited and the true sensitivity and specificity remain to be determined. Our purpose is to describe a ring-enhancing metastasis of adenocarcinoma with a DWI pattern similar to that reported for abscesses. The tumour had a diameter of 1.5 cm and give signal from its centre similar to that of normal brain on T1-weighted images, whereas it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 0 publications
3
28
0
5
Order By: Relevance
“…[3][4][5][6][7] However, exceptions of DWI studies of both pyogenic brain abscesses and necrotic tumors still exit. 7,[9][10][11][12][13][14][15][16] Single-voxel proton MR spectroscopy is useful as an additional diagnostic technique to distinguish pyogenic brain abscesses from necrotic GBMs. [17][18][19][20][21][22] However, aerobic abscesses can simulate intracranial GBMs in single-voxel MR spectroscopy, and MR spectroscopic imaging is useful in the differentiation as additional diagnostic assistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] However, exceptions of DWI studies of both pyogenic brain abscesses and necrotic tumors still exit. 7,[9][10][11][12][13][14][15][16] Single-voxel proton MR spectroscopy is useful as an additional diagnostic technique to distinguish pyogenic brain abscesses from necrotic GBMs. [17][18][19][20][21][22] However, aerobic abscesses can simulate intracranial GBMs in single-voxel MR spectroscopy, and MR spectroscopic imaging is useful in the differentiation as additional diagnostic assistance.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] The cystic or necrotic portion of tumors almost always has a low signal intensity on DWI and a higher apparent diffusion coefficient (ADC) value; however, some exceptions have been reported for necrotic brain tumors. [7][8][9][10][11][12] Hyperintensity with restricted diffusion is diagnostic, but not pathognomonic, for pyogenic abscess on DWI. However, exceptions of DWI studies and substantial variability in the ADCs have been reported for pyogenic abscesses.…”
mentioning
confidence: 99%
“…Özellikle DAG, apselerin malign kistik tümörlerden ayırımında önemlidir (20) . BBA ayrıca metastatik tümörler ve radyasyon nekrozu ile de karışabilmek-tedir (21,22) . Olgumuzda da kranial görüntülemede sağ frontoparietal lobda yüksek gradeli glial tümör rapor edilmiş olmasına rağmen, DAG'da lezyonun santral kesiminde belirgin difüzyon kısıtlanması olan kapsül evresinde apse ile uyumlu kitle lezyonu tanımlanmıştır.…”
Section: Discussionunclassified
“…The rate of water diffusion in the brain tissue is a direct function of its physiological state, and impacted by brain pathologies, such as cerebral infarction. There is an increased restriction to water mobility observed in the area of infarction within the brain tissue, and this produces a bright imaging appearance in the area of cerebral infarction when compared to the other healthy areas of the brain tissue [21]. The observed signal intensity peaks in 3 -4 days and may be persistently high as long as 14 days after the onset of infarction.…”
Section: Methodsmentioning
confidence: 99%